Back stress in strain hardening of carbon nanotube/aluminum composites. Issue 2 (1st February 2018) - Xu, Run; Fan, Genlian; Tan, Zhanqiu; Ji, Gang; Chen, Cai; Beausir, Benoît; Xiong, Ding-Bang; Guo, Qiang; Guo, Cuiping; Li, Zhiqiang; Zhang, Di
ABSTRACT: As demonstrated by the loading–unloading tests and the modeling of the grain size effect and the composite effect, mainly owing to the back stress induced by CNTs, carbon nanotube/aluminum (CNT/Al) composites exhibit higher strain hardening capability than the unreinforced ultrafine-grained Al matrix. The back stress induced by CNTs should arise from the interfacial image force and the long-range interaction between statically stored dislocations and geometrically necessary dislocations around the CNT/Al interface. Therefore, this CNT-induced interfacial back stress strengthening mechanism is supposed to provide a novel route to enhancing the strain hardening capability and ductility in CNT/Al composites. IMPACT STATEMENT The present work investigates the roles and origins of back stress in the strain hardening of the carbon nanotubes/aluminum composites for the first time. GRAPHICAL ABSTRACT: